Cholecystectomy for acute cholecystitis during weekend compared with delayed weekday surgery: A nationwide population cohort study - Edblom, Magnus; Enochsson, Lars; Nyström, Hanna; Sandblom, Gabriel; Arnelo, Urban; Hemmingsson, Oskar; Gkekas, Ioannis (Surgery, 2025)
The optimal timing of surgery for acute cholecystitis has been a subject of debate, but the predominant view supports early cholecystectomy. This study investigated the safety of early cholecystectomy during weekends compared with delayed surgery until a weekday. This was a population-based cohort study based on data from the Swedish National Register for Gallstone Surgery and Endoscopic Retrograde Cholangiopancreatography (GallRiks). Data from 2006 to 2020 were analyzed, and patients with acute cholecystitis were included. Patients who underwent surgery during weekends were compared with patients in hospital during weekends and underwent surgery on any subsequent weekday. Statistical analyses were conducted using logistic regression analysis. 15,730 patients were included, and complications were registered in 2,246 patients (14.3%). The proportion of complications was equal in both groups (14.0% vs 14.5%, P = .365). The proportion of open surgery was higher in the weekend surgery group (29.1% vs 26.3%), with an odds ratio of 1.32 in multivariate logistic regression analysis (P < .001). Meanwhile, the duration of surgery exceeding 2 hours was less common when surgery was performed on the weekend (32.7% vs 46.8%, P < .001, odds ratio: 0.69). In this study, procedures performed during weekends had outcomes that did not substantially differ from those performed during weekdays. The results of our study support performing early cholecystectomies during the weekend without increasing the patients’ risk of complications.